Risk Factors Causing Stunting in Toddlers: A Literature Review - Shofiyah, Alya; Windarti, Siti Wahyu (Journal of Diverse Medical Research: Medicosphere, 2024)
Stunting is a condition in which a child experiences a lack of nutritional intake for a long period of time, causing growth disorders in toddlers (infants under five years old). Stunting in toddlers is a global health problem that is influenced by various social, economic, and policy factors. Objective. This study aims to conduct a systematic review of the available literature to identify risk factors for stunting and examine the challenges faced in handling it, especially in developing countries such as Indonesia and South Africa. In addition, this study also focuses on the role of social policy and health interventions in preventing stunting. Methods. A literature search was conducted on several reputable scientific databases, such as PubMed, Web of Science, and Google Scholar with a span of 2019-2024. Keywords used include "stunting", "socioeconomic risk factors", "health policy", and "stunting management". Articles that meet the inclusion criteria are analyzed to extract data related to study design, population, intervention, outcomes, and conclusions relevant to stunting management in children under five. Results. The review shows that social and economic factors play an important role in stunting, especially in areas with low socioeconomic conditions. Health interventions and social policies have helped reduce stunting rates, but challenges such as lack of access to adequate nutrition and policies that are not fully integrated in some countries remain major obstacles. Conclusions: Although various policies and interventions have yielded positive results in reducing stunting rates, major challenges remain, especially related to access to nutrition and sustainable policy implementation. Future research needs to focus on developing more integrated and personalized policies to reduce stunting rates in developing countries. Keywords: Stunting, Children Under Five, Socioeconomic Risk Factors, Health Policy, Health Interventions, Systematic Review.